2014
DOI: 10.1002/ange.201408220
|View full text |Cite
|
Sign up to set email alerts
|

A Sharp Thermal Transition of Fast Aromatic‐Ring Dynamics in Ubiquitin

Abstract: Aromatic amino acid side chains have a rich role within proteins and are often central to their structure and function. Suitable isotopic‐labelling strategies enable studies of sub‐nanosecond aromatic‐ring dynamics using solution NMR relaxation methods. Surprisingly, it was found that the three aromatic side chains in human ubiquitin show a sharp thermal dynamical transition at approximately 312 K. Hydrostatic pressure has little effect on the low‐temperature behavior, but somewhat decreases the amplitude of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…Recently, new cases have been reported (Weininger et al 2014b;Yang et al 2015) enabled by methodological advances in site-selective 13 C labeling (Lundström et al 2007;Teilum et al 2006), aromatic 13 C relaxation dispersion experiments (Weininger et al 2012(Weininger et al , 2014a and the understanding of strong 1 H-1 H couplings (Weininger et al 2013). Additionally, ring flips can be studied by long scale MD simulations (Shaw et al 2010) and extremely fast ring flips are shown to affect order parameters (Kasinath et al 2015). So far, ring flips in all but one system (Nall and Zuniga 1990) are of aromatic residues without specific interactions, like aromatic-aromatic pair interactions Petsko 1985, 1989) and interactions with cations (Mahadevi and Sastry 2013) or sulfur (Valley et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, new cases have been reported (Weininger et al 2014b;Yang et al 2015) enabled by methodological advances in site-selective 13 C labeling (Lundström et al 2007;Teilum et al 2006), aromatic 13 C relaxation dispersion experiments (Weininger et al 2012(Weininger et al , 2014a and the understanding of strong 1 H-1 H couplings (Weininger et al 2013). Additionally, ring flips can be studied by long scale MD simulations (Shaw et al 2010) and extremely fast ring flips are shown to affect order parameters (Kasinath et al 2015). So far, ring flips in all but one system (Nall and Zuniga 1990) are of aromatic residues without specific interactions, like aromatic-aromatic pair interactions Petsko 1985, 1989) and interactions with cations (Mahadevi and Sastry 2013) or sulfur (Valley et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A connection with the energy of a ring flip is not known. For extremely fast ring flips, that affect order parameters, no sizeable pressure effect was observed (Kasinath et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Phenylalanine residues have been implicated as important markers of dynamical transitions, 7, 31 as motions of bulky aromatic groups often require accommodations of the entire core. 3235 We have recently observed a solvent-driven dynamical transition for a phenylalanine residue in the core of globular villin headpiece subdomain (HP36) that did not entirely disappear in the dry protein, but rather showed a transition temperature which was 80° higher.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of these groups are known to be sensitive not only to local fluctuations but also to the overall hydrophobic core environment. 312 The assessment of the dynamics of aromatic side chains in a protein is relatively technically challenging, and much fewer studies are dedicated to these sites 1323 compared with the investigations of protein methyl groups. Aromatic side chains comprise about 25% of the core volume on average and are often solvent-protected in the core by flanking methyl groups.…”
Section: Introductionmentioning
confidence: 99%